The closed circle: joining and leaving the Muslim Brotherhood in the West - Vidino, Lorenzo (Columbia studies in terrorism and irregular warfare, 2020)
What is the Muslim Brotherhood in the West? -- Joining and leaving the Brotherhood -- Kamal Helbawy -- Ahmed Akkari -- Pierre Durrani -- Mohamed Louizi -- Omero Marongiu -- Pernilla Ouis -- The American Brothers -- Joining and leaving : what the evidence suggests -- The Western Brotherhood's future : from the Arab Spring and beyond.